Understanding the Factors that Influence Digital Readiness in Education: A UTAUT Study among Digital Training Learners - Nguyen, Vinh; Nguyen, Chuyen; Do, Cuong; Ha, Quynh (IPTEK The Journal for Technology and Science, 2025)
Digital transformation is a critical element in modern business operations. Yet, more research needs to be conducted from the perspective of individuals responsible for implementing DT initiatives in their daily work, such as faculty and staff. This study investigates the relationship between digital readiness in education and the constructs outlined in the Unified Theory of Acceptance and Use of Technology (UTAUT) model. We employed a purposive, non-probabilistic sampling strategy to gather data, resulting in 165 observations. The experimental results indicate a significant positive relationship between behavioral intention to adopt digital trans- formation and the behavior of applying digital transformation at work, perceived effectiveness of digi- tal transformation adoption, and facilitating conditions, all in line with the UTAUT model. However, we did not find a significant relationship between effort expectancy or social influence and behavioral intention to adopt dig- ital transformation. Under- standing the factors that impact digital readiness enables universities to develop targeted interventions and support services to promote the successful implementa- tion of DT initiatives in education.